Pelatihan Batik dan Rias untuk Meningkatkan Keterampilan Dasawisma RT 18, RW 03, Kelurahan Kalijaten, Sidoarjo - Trinil Windrowati; Lilis Lestari; Yekti Herlina; Dwi Wahyu Bagas Saputra; Ismi Wijayanti (Yayasan Literasi Sains Indonesia, 2025)
Training on Batik Making Process and Beauty Makeup Techniques to Improve Skills for Dasawisma Group RT 18/RW 03 Kalibader Village, Kalijaten Subdistrict, Sidoarjo is based on the problem of housewives of Dasawisma RT 18/RW 03 Kalibader Village, Kalijaten Subdistrict, Sidoarjo (Partners) with an average education level of junior high school, the majority of whom do not work, so that a lot of free time is usually used to gather/chat in one of the stalls so that it is not economically productive. Partners do not have makeup skills, so when there is an Independence Day celebration (if there is a carnival or performance) it is a hassle to have to go to a beauty salon which requires costs. Through the Beginner Community Service Grant (PMP) from the Directorate of Research and Community Service, Directorate General of Research and Development, Ministry of Higher Education, Science and Technology of the Republic of Indonesia, training was held on the process of making batik and beauty makeup using the methods of socialization, training, technology application, mentoring and evaluation. The results obtained were an increase in knowledge and skills of Partners, and it is hoped that in the future batik skills and makeup techniques can help improve the family economy.